Behavioural Responses of Domestic Animals for Adapting to Thermal Stress - Fonsêca, Vinícius F. C. [UNESP]; Saraiva, Edilson P.; Dos Santos, José D. C.; da Cunha Morais, Larissa Kellen; Nascimento, Sheila T.; De Melo Costa, Cíntia C. [UNESP]; Moura, Gustavo B. [UNESP]; Neta, Geni Caetano Xavier [UNESP]; Bícego, Kênia C. [UNESP]; Sejian, Veerasamy; Neto, Marcos Chiquitelli [UNESP]; Maia, Alex S. C. [UNESP] (Springer Nature, 2022)
Animals use behaviour to alleviate the feelings of hot and cold, by avoiding situations that arouse those feelings. That is the basis of behavioural thermoregulation. By employing behavioural thermoregulation, domestic animals can manipulate heat exchanges between body surface and surrounding environment, thus reducing demands for evaporative water loss and heat production in order to regulate body temperature. Availability of buffered microclimates and possibility for animals to employ behavioural thermoregulation is of utmost importance for those that have a high surface area to volume ratio. By observing the animal’s behaviour, farmers can easily predict how animals are coping with thermal challenges and to get insights about their preferences. This chapter briefly discusses the importance of behavioural thermoregulation under the context of domestic animals. Specifically, (1) the association between body size and relevance of thermoregulatory behaviour; (2) evidences on how shade or shelter-seeking behaviour and body orientation adjustments helps neonates and adult animals to save water and energy; and ultimately (3) to prospect future studies involving behavioural thermoregulation of free-ranging livestock, particularly to better predict how they use some kind of behavioural plasticity to buffer direct and indirect impact of climate change.
Keywords: Animal behaviour; Climate change; Heat stress; Thermoneutral zone; Thermoregulation